Abstract ID: 118 Internal dosimetry of 68Ga-DOTATATE using Monte Carlo GATE simulation for XCAT phantom. (October 2017) - Mokri, Mersede; Ay, Mohmmad Reza; Taghizade, Sima; Ebrahimi, Marzieh; Geramifar, Parham
Abstract : Introduction: Widespread use of FDG PET/CT imaging leads to improvement in non-FDG- avid somatostatin receptor imaging of tumor tissue. These synthetic somatostatin analogs can be labeled with β -emitting radionuclides, such as 68 Ga[1], but estimating the absorbed dose in critical organs is important. The aim of this research is to calculate absorbed dose in all organs especially pituitary gland and thymus in 68 Ga-DOTATATE dosimetry. Materials and Methods: Two total body male and female XCAT phantoms with 128 × 128 matrix size and 600 slices containing 1 mCi activity of 68 Ga was simulated. GATE Monte-Carlo code was employed for dosimetry calculations. Based on MIRD schema, we reported s-values of self-absorption and cross-irradiation in spleen, bladder, kidneys and liver, as well as cross-irradiation in pituitary gland and thymus. Results: We reported the S-value for spleen, the most critical organ in 68 Ga-DOTATATE to be 13.7e−004 mGy/MBq-s and 15.6e−004 mGy/MBq-s in male and female phantom respectively. The highest amount of cross-irradiation in spleen is from kidney with the amount of 0.097e−004 mGy/MBq-s. The amount of self-absorption is in Bladder with 42.1e−004 mGy/MBq-s and 50e−004 mGy/MBq-s in male and female phantom respectively. The absorbed dose in thymus from spleen is 2.3710e−006 mGy/MBq-s in male and 3.1138e−006 mGy/MBq-s in female. Absorbed dose of pituitary gland from spleen is 0.53e−007 mGy/MBq-s. Conclusion: We performed internal dosimetry using XCAT phantoms and GATE Monte-Carlo code for 68 Ga. Our results could be helpful in estimating absorbed dose in critical organs specially those not being considered in conventional methods.